Cognitive and Communicative performances of children from 3 to 5 years old with Language Delay - DJELLE, Opely Patrice-aime (Advances in Social Sciences Research Journal, 2020)
This research deals with the cognitive and communicative performances of children from 3 to 5 years old with language delay. Our objective is to observe the 3 to 5 year old child with language delay integrating and interacting socially, in an environment other than his family during his interactions with his peers and especially with the adult. . We conducted the study in the light of the theories of Piaget, Vygotsky and the Anglo-Saxon theory on the extent of language disorders. The implementation of language activity by several approaches around games and textless books and the observation of these in interaction with their specialized educators including trainees as well as their peers, allowed the rating of 5 children ( 3 boys and 2 girls, all with language delay) on an observation grid. The success of the exchange is largely assured thanks to the interventions of specialized educators (ES) to support the speech of the children. Despite their delay, these children are aware of their social environment, and integrate into the rehabilitation program, and particularly into language activities.